Urban Trajectories and Posturing: The Place of Children and Teenagers in the Makeup of the City - Monnet, Nadja; Boukala, Mouloud (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2018)
Research Framework: Many authors prefer to focus on the acrimonious relationship that exists between children and the city. This narrative is given as a story of eviction, particularly in the latter half of the 20th century, and the ubiquitous arrival of motorized traffic ; a phenomenon that has only accelerated over time. It is a radical separation between a before, which represents a golden age for children where the city revolved around them, and an after were children are represented as being shut in at home, forbidden from playing in the street and connected to the world via their smartphones and tablets. Despite this alarmist discourse, it is important to remember that children and teenagers continue to explore and socialize within their cities regardless of whether they are not (or are no longer) in the majority. Objectives : This introductory article to “Exploring the City : Children and Teenagers’ Relationship with Public Spaces” is designed to present the state of research as well as paths of reflection and innovative actions on how children and teenagers experience the city, the way they act and how they are influenced by contemporary spaces. Methodology : The introductory article is based on a review of work done in the fields of anthropology, history, geography, architecture and urban studies, all of which discuss the relationship between urban spaces and children and teenagers. This analysis is juxtaposed by ongoing projects that ask the opinions of youths to establish a consensus-building approach to urbanism and urban redevelopment in cities, metropolises and megacities. Results : By including all age groups (children and teenagers) as well as the types of spaces that are generally kept separate, the articles presented herein ask us to consider several important aspects including : the presence of youths in urban spaces, the standardization, regulation and gamification of certain public spaces ; the appeal of closed spaces (interiors, shopping centres) and their appropriation ; the practise of physical activities ; autonomous mobility ; the interest in digital media and familial injunctions to assess the influence of parents and siblings on the relationships that young people have with the city.Conclusions : This article focuses on the necessity of taking an intersectional approach that considers a broad range of variables including gender, age and socio-geographical origin, race in particular, to analyze the relationships between children and teenagers and public spaces. Here we reveal the importance of the passage between interior spaces (homes, schools, youth homes, recreational centres, etc.) and exterior spaces, whether the exploration of streets, parks, gardens and shopping malls remains possible as well studying the relations and tension that exist between families and children, between youths and the managers of these spaces, between youths with and without adult supervision and between youths and adult users of public spaces as both actors and witnesses.Contribution: This article takes a look at the societal and anthropological issues that affect the relationship between public spaces and children and teens in over a dozen cities located in Europe, North America, Northern Africa and the Middle East. It identifies paths of exploration and paths of implementation on this topic.